2014
DOI: 10.1093/mnrasl/slu089
|View full text |Cite
|
Sign up to set email alerts
|

Serendipitous discovery of a thin stellar stream near the Galactic bulge in the Pan-STARRS1 3π Survey

Abstract: We report the discovery of a thin stellar stream found in Pan-STARRS1 photometry near the Galactic bulge in the constellation of Ophiuchus. It appears as a coherent structure in the colour-selected stellar density maps produced to search for tidal debris around nearby globular clusters. The stream is exceptionally short and narrow; it is about 2.5 • long and 6 ′ wide in projection. The colour-magnitude diagram of this object, which harbours a blue horizontalbranch, is consistent with an old and relatively meta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 43 publications
1
42
0
1
Order By: Relevance
“…However, further insight can be obtained from the known kinematics of the star (see Table 1) and about half of the candidate GCs with matching metallicity (D. Casetti 2 ). We proceed under the assumption that the progenitor cluster is still intact, while evidence has also been found in the inner halo for disrupted GCs (Bernard et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, further insight can be obtained from the known kinematics of the star (see Table 1) and about half of the candidate GCs with matching metallicity (D. Casetti 2 ). We proceed under the assumption that the progenitor cluster is still intact, while evidence has also been found in the inner halo for disrupted GCs (Bernard et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recent surveys have discovered dynamically cold tidal debris of many disrupted stellar systems-likely globular clusters or low mass dwarf galaxies-in the inner tens of kiloparsecs of the Milky Way (Grillmair 2010(Grillmair , 2014Bonaca et al 2012;Bernard et al 2014;Koposov et al 2014;Martin et al 2014). These debris, arranged in thin streams of stars, are powerful probes for the structure of our own galaxy.…”
Section: Introductionmentioning
confidence: 99%
“…This effect has been invoked by Sesar et al (2016) to explain the puzzling orbit and length of the recently observed Ophiuchus stream (Bernard et al 2014;Sesar et al 2015). This suggests that spherical potentials are no longer suitable for modeling tidal streams.…”
Section: Introductionmentioning
confidence: 99%
“…The recently found cold (velocity dispersion 1 v ⪅ s km s −1 ) Ophiuchus stream (Bernard et al 2014), presents a puzzle in this respect: its stellar population is old (∼12 Gyr), yet it is on an orbit with an orbital period P 350 Myr » and it is apparently only 1.6kpc long (Sesar et al 2015, hereafter S15). To maintain such a short length, the observed debris should have been disrupted only within the last 250 million years.…”
Section: Introductionmentioning
confidence: 99%